At the Speed of Light: Recent Advances on Photocatalyzed Generation and Applications of Iminyl Radicals Promoted by Visible-light - Valle-Sánchez, Mario; López-Saladino, Osvaldo F.; González-Rivas, Nelly; Estévez-Martínez, Yoxkin; Frontana-Uribe, Bernardo A.; Cuevas-Yañez, Erick (Current Organic Chemistry, 2024)
Nitrogen-positioned radicals are chemical entities that have a lengthier history than carbon ones and their high reactivity makes them invaluable. But, despite its power, much of its chemistry is still uncharted. Currently, developed methodologies to access nitrogen-positioned radicals, such as transition metal catalysis or visible-light photoredox methods through a single-electron transfer process, avoiding the use of harmful or toxic reagents, excess raw materials, solvents as well as pre-functionalization steps or extensive synthetic routes are in continuous progress. This revision aims to depict the recent advances in the field of iminyl-radicals' syntheses, a special class of radicals placed on nitrogen, catalyzed by transition metals or photoredox techniques for the construction of C-N bonds and their synthetic applications. This work serves as a comprehensive guide for the scope of synthetic applications that this kind of radicals could have.
Keywords: C-N bonds